2018
DOI: 10.1111/ijcp.13095
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine may be associated with reduced risk of coronary artery diseases in patients with rheumatoid arthritis: A nationwide population-based cohort study

Abstract: This study revealed association of decreased CAD risk in RA patients taking HCQ. The protective effect of HCQ on CAD is consistent regarding subgroup analysis on age, gender and different comorbidities groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…Despite its relatively delayed onset of action, its touted benefits in reducing cardiovascular morbidity in patients with RA have been recognized, making it a good second-line DMARD therapy for patients with inadequate response to methotrexate. 9 The demand surge for hydroxychloroquine severely affected access to this drug among patients with SLE and RA. 10 Then on 22 May 2020, while this survey was being conducted, a study by Mehra et al 11 concluded that use of drug regimens of chloroquine or hydroxychloroquine alone or in combination with a macrolide was associated with an increased hazard for clinically significant occurrence of ventricular arrhythmias and increased risk of in-hospital death with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its relatively delayed onset of action, its touted benefits in reducing cardiovascular morbidity in patients with RA have been recognized, making it a good second-line DMARD therapy for patients with inadequate response to methotrexate. 9 The demand surge for hydroxychloroquine severely affected access to this drug among patients with SLE and RA. 10 Then on 22 May 2020, while this survey was being conducted, a study by Mehra et al 11 concluded that use of drug regimens of chloroquine or hydroxychloroquine alone or in combination with a macrolide was associated with an increased hazard for clinically significant occurrence of ventricular arrhythmias and increased risk of in-hospital death with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the adverse risk of HCQ, some reports have bared out HCQ showed protective effect on coronary artery, dyslipidemia, diabetes mellitus, preeclampsia, and chronic inflammatory diseases and so on. A clinical trial in Taiwan (registration number: CSMUH CS15134) confirmed that HCQ users versus non-users for coronary artery diseases events was 0.32 (95% CI, P <0.01) over up to 10 years (Hung et al, 2018). This study revealed that RA patients taking with HCQ could decrease coronary artery diseases risk, while the dosage of HCQ was not clearly.…”
Section: Potential Risk Of Hcq In Clinic To Treat Covid-19mentioning
confidence: 71%
“…Hydroxychloroquine (HCQ) has long been used to reduce inflammation in patients with RA and lupus. In a nationwide cohort study, HCQ use was associated with decreased CAD risk in the RA population (59). Besides, an OXI trial (NCT02648464) is currently underway to study the effect of HCQ on the prevention of recurrent cardiovascular events among MI patients (60).…”
Section: Targeting the Central Pathway (Il-1β Tnf-α Il-6)mentioning
confidence: 99%